Sosialisasi Metode Story Teling Dalam Peningkatan Kemampuan Bahasa Inggris Menggunakan Perangkat Multimedia di SMK Muhamdiyah 2 Palembang - Uzer, Yuspar; H, Herlina; M, Marleni; Hidayad, Ferri; Uzer, Yus Vernandes (Yayasan Daarul Huda Kruengmane, 2024)
Storytelling or storytelling is an imaginary story that is considered not to have really happened, either by the teller or by the listener. Fairy tales are not bound by normative and factual provisions regarding actors, time and place. The perpetrators are imaginary creatures who have the wisdom or lack thereof to arrange human problems in all kinds of ways. Fairy tales are told mainly for entertainment, although many also depict truth or even morals. From the description above, the researcher concludes that storytelling or storytelling is a type of prose in old Malay literature that does not really happen in relation to the social environment. and passed down orally from one generation to the next. This community service is carried out as an embodiment of the implementation of the Tri Dharma of Higher Education for Lecturers at PGRI University in Palembang and L2 Dikti Palembang. The target to be achieved in the implementation of Community Service (PKM) is that lecturers can apply and develop their academic skills. Apart from that, after participating in this training, students are expected to be able to perform live and written English conversations so that students can speak English fluently. fluent, communicative and intelligent in using English with the title Socialization of the Storytelling Method in Improving English Language Skills Using Multimedia Devices at SMK MUHAMDIYAH 2 Palembang